INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2009–2017 - Agusta, Christina; Radianto, Wirawan E.D. (Accounting Study Program, Universitas Ciputra Surabaya, 2019)
This purpose of this research is to analyze the impact of intellectualcapital on the companies performance. The research used quantitativeapproach, and it collected by annual reports to pharmaceutical company atIndonesia Stock Exchange (IDX) from year 2009–2017 which had a populationof 10 companies. The hypothesis of this research is tested by usingmultiple regression analysis. The result indicate that (1) intellectual capitalhas positive influence to the companies performance (ROA and ROE); (2)intellectual capital has negative influence on companies performance (ATOand MBV). Hence, to maximize the performance on pharmaceutical companiesmerely consider intellectual capital factors.